An Analysis of Educational Values in the Book At-Tarbiyah al-Islamiyyah wa Falasifatuha by Muhammad ‘Athiyah al-Abrasyi - Anwar, saiful; Puji Astutik, Anita; Habibah Imtinan , Fairuz (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2025)
Classical Islamic educational thought has made significant contributions to the development of an education system rooted in moral, spiritual, and intellectual values. One of the prominent figures in this field is Muhammad ‘Athiyah al-Abrasyi, whose work At-Tarbiyah al-Islamiyyah wa Falasifatuha presents profound ideas regarding the aims, principles, and methods of Islamic education. This study aims to analyze the educational values contained in the book and examine their relevance to contemporary Islamic education. This research employs a qualitative approach using the library research method. The primary source is al-Abrasyi’s original work, supported by secondary sources including books, journals, and previous studies. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that the core values of education in al-Abrasyi’s perspective include moral education as a fundamental pillar, balanced preparation for both worldly and hereafter life, and the holistic development of individual potential. Furthermore, he emphasizes contextually appropriate educational methods such as advice, exemplary conduct, and moral evaluation. Al-Abrasyi’s ideas remain highly relevant to contemporary Islamic education, particularly in integrating Islamic values into curricula, affirming the teacher’s role as a moral model, and developing adaptive yet value-oriented curricula.